Teachers' Perspectives on task-based language teaching in tieng Anh 10&11 by Hoang Van Van: From the textbook to the classroom - Trần Thị Thùy Ngân (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This piece of research aims to investigate the teacher‟s perspectives of TBLT approach applied in “Tieng Anh 11” and “Tieng Anh 10” in the ten-year textbook series by Hoang V. Van and how communicative and task-like the activities are designed in these textbooks. Moreover, Vietnam and how teachers interpreted and